2022
DOI: 10.3389/fbioe.2022.881979
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Effects of a Novel Anatomic Titanium Mesh Cage for Single-Level Anterior Cervical Corpectomy and Fusion: A Finite Element Analysis

Abstract: Background: The traditional titanium mesh cage (TTMC) has become common as a classical instrument for Anterior Cervical Corpectomy and Fusion (ACCF), but a series of complications such as cage subsidence, adjacent segment degeneration (ASD), and implant-related complications by using the TTMC have often been reported in the previous literature. The aim of this study was to assess whether a novel anatomic titanium mesh cage (NTMC) could improve the biomechanical condition after surgery.Methods: The NTMC model c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 32 publications
3
21
0
Order By: Relevance
“…The self-tapping screws were 16 mm long. Additionally, convergence analysis was performed to ensure that the maximum changes in the strain energy were <3% and showed that when the element size was between 0.1 and 1, the error stabilized at a minimum value, i.e., less than 3%, which is concordant with previous studies ( Jones and Wilcox, 2008 ; Ayturk and Puttlitz, 2011 ; Zhang et al, 2022b ). The material properties of the bone graft and newly formed bone were set as the cortical bone ( Figure 1 ).…”
Section: Methodssupporting
confidence: 87%
See 4 more Smart Citations
“…The self-tapping screws were 16 mm long. Additionally, convergence analysis was performed to ensure that the maximum changes in the strain energy were <3% and showed that when the element size was between 0.1 and 1, the error stabilized at a minimum value, i.e., less than 3%, which is concordant with previous studies ( Jones and Wilcox, 2008 ; Ayturk and Puttlitz, 2011 ; Zhang et al, 2022b ). The material properties of the bone graft and newly formed bone were set as the cortical bone ( Figure 1 ).…”
Section: Methodssupporting
confidence: 87%
“…However, the current study aimed to provide a trend instead of natural status. Several recent studies have adopted similar methods in developing the finite element spine model and reported acceptable results ( Wu et al, 2019 ; Liang et al, 2022 ; Zhang et al, 2022b ). Third, the geometry of the human spine varies among individuals, while the model of this present study was developed on the basis of the data from a single patient.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations